On-Demand Bioadhesive Dendrimers with Reduced Cytotoxicity - Gao, Feng (2018)
Tissue adhesives based on polyamidoamine (PAMAM) dendrimer, grafted with UV-sensitive aryldiazirine (PAMAM-g-diazirine) are promising new candidates for light active adhesion on soft tissues. Diazirine carbene precursors form interfacial and intermolecular covalent crosslinks with tissues after UV light activation that requires no premixing or inclusion of free radical initiators. However, primary amines on the PAMAM dendrimer surface present a potential risk due to their cytotoxic and immunological effects. PAMAM-g-diazirine formulations with cationic pendant amines converted into neutral amide groups were evaluated. In vitro toxicity is reduced by an order of magnitude upon amine capping while retaining bioadhesive properties. The in vivo immunological response to PAMAM-g-diazirine formulations was found to be optimal in comparison to standard poly(lactic-co-glycolic acid) (PLGA) thin films.